Um estudo sobre as palavras cantada, falada e declamada e seus efeitos impressivos - Lomba, Juliana Andreassa da (2017)
This research endures the challenge of approaching the faces and interfaces of three styles of oral language. Its objectives are: to investigate the differences and similarities among the sung, spoken and recited styles as stylistic forms of oral language and social expression and to analyze their impressive effects, since the sung, spoken and recited styles have different expressive purposes. To reach the proposed objectives two types of analysis were combined: acoustic and perceptive. The acoustic analysis was used to verify the differences of production among the three styles, while the perceptive analysis, which implied on the application of a semantic differential questionnaire to a group of judges, was used to investigate the impressive impact of the mentioned styles sonorities. By the acoustic analysis it was possible to verify, through the fundamental frequency measures, intensity, duration and spectral decline, the prosodic characteristics of each one of the styles. By the perceptive analysis, the presented results show how each style reaches the listeners in a different way, since the evaluation of the selected descriptors to evaluate them was differential, which evinced different impressive effects. The acoustic and perceptive analysis results were correlated by using statistics tests of multidimensional analysis. The sung, spoken and recited styles prosodies present different aspects, as was shown by the generated values in the script ExpressionEvaluator (BARBOSA, 2009). Therefore, we conclude that the sung, spoken and recited styles cause different impressive effects that activate the organism in different ways and they have the communication as a social role